2012
DOI: 10.2139/ssrn.2017456
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between an Independent Audit and Financial Reporting Quality: Evidence from Small Private Commercial Banks

Abstract: The study starts by examining whether the decision to have an independent audit is systematic and endogenous. Private commercial banks with under $500 million in total assets are regulatory exempt from an independent audit requirement.However, approximately 56% of these small private commercial banks voluntarily decided to have an independent audit. Utilizing a set of machine learning algorithms, Ifind that the decision to have an independent audit is systematically determinable and is endogenously determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Researchers demonstrated that there are connections between the type of audit report and the auditors' awareness or even unconscious interests or factors (Chan & Kogan, 2012;Constantinides, 2002;Geiger & Raghunandan, 2002;Moore et al, 2003;Rosman, 2011;Tara, 2011 Based on these researchers' findings and on our analysed case results, we suggest that the independence of financial auditing could be improved by finding solutions that eliminate, as much as possible, the material connections between the auditors and those being audited.…”
mentioning
confidence: 58%
“…Researchers demonstrated that there are connections between the type of audit report and the auditors' awareness or even unconscious interests or factors (Chan & Kogan, 2012;Constantinides, 2002;Geiger & Raghunandan, 2002;Moore et al, 2003;Rosman, 2011;Tara, 2011 Based on these researchers' findings and on our analysed case results, we suggest that the independence of financial auditing could be improved by finding solutions that eliminate, as much as possible, the material connections between the auditors and those being audited.…”
mentioning
confidence: 58%